PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASIONAL DENGAN VARIABEL MODERATING KEPUASAN KERJA PEGAWAI RUMAH SAKIT SWASTA DI PKU MUHAMMADIYAH SURAKARTA - -, Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2009)
ABSTRACT The research examined the moderation effect of job satisfaction on the influence of transformational leadership toward organizational commitment. The research uses population research consist of 152 respondents take to all employee’s of PKU Muhammadiyah Hospital in Surakarta. The data were collected with questionnaire, while the data analysis uses Regression Analysis with residual absolute test. This results of this research showed that transformational leadership had effect on organizational commitment, job satisfaction had effect on organizational commitment. Furthermore, the findings supported the research hypothesis that job satisfaction had a positively and significantly as a moderating variable on the influence of transformational leadership toward organizational commitment. Keywords: transformational leadership, organizational commitment, and job satisfaction.